Eileen Gray’s Jean Désert showroom 217 Rue du Faubourg Saint-Honoré, Paris ; marketing design in the 1920s - Tim Benton (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The Irish designer Eileen Gray (1878-1976) is recognized as one of the foremost artists of the 1920s. Detailed analysis of the accounts of the Jean Désert showroom in Paris, opened by Gray in 1922, adds to our understanding of her approach to design and marketing. The showroom did not only fail due to low turnover but also due to the high fixed costs involved in subsidising the lacquer workshop run by Seizo Sougawara and the rug workshop managed by Evelyn Wyld. The article addresses the following questions: What was the financial viability of the showroom? Who were Gray’s clients? What kinds of items sold best? What does the showroom tell us about Gray’s approach to design? How does her practice differ from that of other designers of the day? What clues do the documents give to understanding Gray’s clients and their social milieu?